The Government's Role In Building Notary Professionalism - Mustiqo Vitra Ardhiansyah; Jusuf Irianto (LEGAL BRIEF, 2022)
A notary is one of the legal professions that requires public trust, so a notary must be able to act professionally. Professionalism can be formed if the Notary in carrying out his duties remains guided by the Notary code of ethics and the Notary Position Act and utilizes information technology. However, the fact is that recently there have been many cases of violations committed by Notaries which ultimately violate the code of ethics and the Law on Notary Positions. For this reason, the role of the Government in minimizing violations in order to foster a professional attitude is very much needed. Based on these reviews, this study aims to examine the Government's efforts in building Notary professionalism. This study uses a normative juridical approach with data collection techniques through literature study. This study concludes that in building Notary professionalism, the Government, namely the President of the Republic of Indonesia together with the House of Representatives,stipulation of laws and regulations concerning Notary Positions, regulations concerning the establishment of the Notary Supervisory Council and Notary Honorary Council, regulations concerning the use of AHU Online, conducting guidance and supervision, as well as routine inspections. Meanwhile, if the Notary has violated the code of ethics, these agencies seek to impose sanctions as a follow-up to the violation.